2018
DOI: 10.1101/503953
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The importance of selected markers of inflammation and blood-brain barrier damage for short-term post-stroke prognosis

Abstract: Acute cerebral ischemia triggers local and systemic immune response. The aims of this project was to assess the blood serum concentration of the markers of inflammation and markers of the blood brain barrier damage on the first day of ischemic stroke, and the mutual correlations between these marker levels. Methods Our prospective study included 138 patients with first-in-life stroke, who were analyzed according to: plasma concentration of the following markers on the first day of stroke: Il-2 and IL-6, S100B,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
74
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(109 citation statements)
references
References 54 publications
7
74
1
5
Order By: Relevance
“…To date, a number of studies have demonstrated that the blood levels of cytokines, chemokines, and growth factors, including C-reactive protein, TNF-α, IL-6 and IL-10, are associated with outcomes in AIS patients [14][15][16]. Although IL-2 is one of the most frequently studied cytokines in stroke patients, the conclusions are ambiguous and inconsistent with the results of experimental studies [17][18][19]. This might be due to the complexity of IL-2/IL-2R autocrine loops.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a number of studies have demonstrated that the blood levels of cytokines, chemokines, and growth factors, including C-reactive protein, TNF-α, IL-6 and IL-10, are associated with outcomes in AIS patients [14][15][16]. Although IL-2 is one of the most frequently studied cytokines in stroke patients, the conclusions are ambiguous and inconsistent with the results of experimental studies [17][18][19]. This might be due to the complexity of IL-2/IL-2R autocrine loops.…”
Section: Discussionmentioning
confidence: 99%
“…When the brain is injured and ischemic, the blood-brain barrier is damaged, which aggravates brain edema, ischemia and hypoxia, and further causes brain tissue damage (Lasek-Bal et al, 2019). The destruction of the blood-brain barrier is a key link in the aggravation of secondary brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, our cohort of patients with non-NSA-ESUS had lower levels of CRP in comparison with strokes due to atherosclerosis; instead NSA-ESUS seem to have intermediate values, but not significantly different in comparison with both non-NSA ESUS and atherosclerotic strokes. It is well-known the pathogenic link among inflammation, atherosclerosis, and arterial stiffness (24), thus these intermediate values suggest a further similarity between NSA-ESUS and strokes due to atherosclerosis.…”
Section: Discussionmentioning
confidence: 84%